Estimation of changes in the reservoir reflection coefficient due to CO2 injection at Ketzin Site, Germany - Yang, C.; Juhlin, Christopher; Fan, W.; Ivanova, A. (Society of Petroleum Engineers, 2011)
Seismic amplitude information and data from an injection well (IW) and an observation well (OW2) are used to estimate reflection coefficients. Seismic volumes are extracted near the two boreholes from a baseline and a monitor survey. An anhydrite layer above the reservoir generates a high amplitude reflection and this is used for calibration. The amplitude equation of Ghaderi and Landro (2009) is used to estimate R0 for the reservoir. In the IW it is between 0.1-0.12 and in OW2 it is between 0.1-0.14 for the baseline survey. These values correspond well to logging data, providing confidence in our approach. We use the same method on the monitor survey and find R0 in the IW is now in the range 0.26-0.31 and R0 in OW2 is now 0.13-0.16, indicating lower CO2 saturation in OW2.